Effect of collagen sponge and fibrin glue on bone repair - Thiago de Santana SANTOS; Rodrigo Paolo Flores ABUNA; Adriana Luisa Gonçalves de ALMEIDA; Marcio Mateus BELOTI; Adalberto Luiz ROSA (University of São Paulo, 2015)
ABSTRACT The ability of hemostatic agents to promote bone repair has been investigated using in vitro and in vivo models but, up to now, the results are inconclusive. Objective In this context, the aim of this study was to compare the potential of bone repair of collagen sponge with fibrin glue in a rat calvarial defect model. Material and Methods Defects of 5 mm in diameter were created in rat calvariae and treated with either collagen sponge or fibrin glue; untreated defects were used as control. At 4 and 8 weeks, histological analysis and micro-CT-based histomorphometry were carried out and data were compared by two-way ANOVA followed by Student-Newman-Keuls test when appropriated (p≤0.05). Results Three-dimensional reconstructions showed increased bone formation in defects treated with either collagen sponge or fibrin glue compared with untreated defects, which was confirmed by the histological analysis. Morphometric parameters indicated the progression of bone formation from 4 to 8 weeks. Additionally, fibrin glue displayed slightly higher bone formation rate when compared with collagen sponge. Conclusion Our results have shown the benefits of using collagen sponge and fibrin glue to promote new bone formation in rat calvarial bone defects, the latter being discreetly more advantageous.